Photocatalysis : applications - Dionysiou, Dionysios D.; Puma, Gianluca Li; Ye, Jinhua; Schneider, Jenny; Bahnemann, D. (RSC energy and environment series, 2016)
From environmental remediation to alternative fuels, this book explores the numerous important applications of photocatalysis. The book covers topics such as the photocatalytic processes in the treatment of water and air; the fundamentals of solar photocatalysis; the challenges involved in developing self-cleaning photocatalytic materials; photocatalytic hydrogen generation; photocatalysts in the synthesis of chemicals; and photocatalysis in food packaging and biomedical and medical applications. The book also critically discusses concepts for the future of photocatalysis, providing a fascinating insight for researchers. Together with Photocatalysis: Fundamentals and Perspectives, these volumes provide a complete overview to photocatalysis.